Pharmacokinetics behavior of four cannabidiol preparations following single oral administration in dogs - Limsuwan, Sasithorn; Phonsatta, Natthaporn; Panya, Atikorn; Asasutjarit, Rathapon; Tansakul, Natthasit (Frontiers in Veterinary Science, 2024)
Cannabidiol (CBD) is a natural phytochemical agent and one of the most abundant found in Cannabis sativa. It is known to exhibit pharmacological properties on various condition such as relieving-inflammation, pain, epilepsy, and anxiety effect. There has been an increasing trend globally in the use of CBD as a supplement in pets. Consequently, there are various CBD products being marketed that are specifically available for pets. Veterinarians and pet owners are concerned that following ingestion, different CBD formulations may result in a CBD level circulating in the blood that may affect the safe use and efficacy of CBD in pets. Several pharmacokinetics studies in animals have been mainly conducted with an oily form of CBD. To date, there is a lack of data regarding direct comparisons in animals among the CBD plasma kinetic profiles from an oral administration of the various preparation forms. Therefore, the current study evaluated and compared the plasma CBD levels from a single oral administration using four different CBD preparations—liquid (an oil-based form, a nanoemulsion form, or a water-soluble form) or a semi-solid form (as CBD mixed in a treat) in dogs. In total, 32 healthy, cross breed dogs were randomly assigned into 4 groups and treated according to a 1-period, 4-treatment parallel-design. The three liquid forms were dosed at 5 mg/kg body weight, while the single semi-solid form was given at 50 mg/treat/dog. The results showed that the CBD plasma profile from the administration of a water-soluble form was comparable to that of the oil-based group. The nanoemulsion-based form tended to be rapidly absorbed and reached its peak sooner than the others. However, the CBD in all preparations reached the maximum plasma concentration within 3 h post-dose, with an average range of 92–314 µg/L. There were significant differences among certain parameters between the liquid and semi-solid forms. This was the first study to provide pharmacokinetics data regarding CBD in water soluble, nanoemulsion-based, and semi-solid forms for dogs as companion animals. The current data should facilitate the scrutiny of CBD plasma profiles based on different formulations via an oral route in dogs.